Remotely induced warming of Antarctic Bottom Water in the eastern Weddell gyre - Couldrey, MP; Jullion, L; Garabato, AC; Rye, C; Herraiz Borreguero, L; Brown, PJ; Meredith, MP; Speer, KL (Geophysical Research Letters, 2013)
Four repeat hydrographic sections across the eastern Weddell gyre at 30E reveal a warming (by ~0.1C) and lightening (by ~0.02-0.03 kg m-3) of the Antarctic Bottom Water (AABW) entering the gyre from the Indian sector of the Southern Ocean between the mid-1990s and late 2000s.Historical hydrographic and altimetric measurements in the region suggest that the most likely explanation for the change is increased entrainment of warmer mid-depth Circumpolar Deep Water by cascading shelf water plumes close to Cape Darnley, where the Indian-sourced AABW entering the Weddell gyre from the east is ventilated. This change in entrainment is associated with a concurrent southward shift of the Antarctic Circumpolar Currents (ACC) southern boundary in the region. This mechanism of AABW warming may affect wherever the ACC flows close to Antarctica.